Automated Teachers No More: A Closer Look into Teachers’ Role in Postmethod Era - Padilla, Joseph E.; Padilla, Corazon A. (Silliman Journal, 2022)
This paper discusses the perceived roles of teachers explicated from the principles of postmethod pedagogy proposed by Kumaravadivelu (2001). This review of an article published in TESOL Quarterly Vol. 35, No. 4 by Kumaravadivelu (2001) entitled Toward a Postmethod Pedagogy highlights some salient points and directions set by postmethod as a response to increasing dependence on method-based language teaching. Here, we situated the facets of postmethod in the Philippine setting as well as experiences from other foreign language classrooms. The focus of the review was on the perceived roles of English Language Teachers (ELT) in the postmethod era. There are three derived key characteristics of teachers: postmethod teachers are autonomous, they have a sense of plausibility, and they are educators who legitimize voices and visions of prospective teachers. In brief, teachers in the postmethod have to be theorizers of their practices. Reflective teaching must be emphasized to address issues in the classrooms. Since no method is considered best, teachers should reconsider developing their own contextualized strategies to maximize learning opportunities.